Kinetic and equilibrium studies on the removal of Cu(II) from aqueous solutions using coco peat subjected to different soaking ages - Tanyag, Darryl Neil O.; Tanchuling, Maria Antonia N. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Coco peat is an abundant and low cost byproduct of coconut industries. Due to its high adsorption capacity, it is being used as a filter material in small scale wastewater treatment systems. Numerous studies have proven the effectiveness of coco peat as a sorbent material. In this study, the effect of the soaking age on its sorption capacity was evaluated using batch experiment. With copper solution as the adsorbate, the parameters studied in this experiment were pH, contact time, initial concentration, and the soaking age. The pH levels tested were 2.4, 4.0, and 6.0. The initial concentration ranges from 10 to 150 ppm, and the range of contact time is 5 to 200 minutes. The mechanism of sorption and the initial sorption rate were determined using the pseudo-second order kinetic model. The Langmuir and Freundlich isotherm models were used to describe the type of adsorption on the adsorbent surface and the adsorption capacity. The results of the experiment indicate that the removal is higher at pH 6.0. The higher number of Hydrogen ions in the acidic solutions caused a decrease in the available active sites at the surface of the coco peat particles. For the initial concentration, it was observed that as the initial concentration increases, the removal percentage decreases. The kinetic data fits the linear form of the pseudo-second order model indicating that the rate-controlling step is chemisorption, where the removal from a solution is due to physicochemical interactions between the two phases. For the effect of soaking age, the adsorption capacities of the different columns were compared and there was no observable trend relating the soaking age to the sorption capacity. The equilibrium data fits the linear fonn of the Freundlich isotherm. The type of adsorption is heterogeneous at various active sites on the surface of the adsorbent. Unlike the Langmuir isotherm, the amount of copper ions on the active sites cannot be predicted.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Coir; Copper -- Absorption and adsorption